Kānʻanurak sathāpattayakam, pratimākam, læ čhittrakam nai Phetchaburī (Sun Watthatham Čhangwat Phetchaburī, Witthayālai Khrū Phetchaburī, 1990)
On conservation of architecture, sculpture, and painting of Phetchaburi Province, Thailand; contributed articles.